(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article examines the importance of tactical systems and methods of development in the training of football players. Tactics slowly, but with incre asing speed, begins to influence the development of the football game without deviations and takes the leading place among other components, and planning and organization according to the result of properly oriented training. new interrelationships are required in compliance with the principle of unity of general and special training.